2018
DOI: 10.1055/s-0038-1675831
|View full text |Cite
|
Sign up to set email alerts
|

Do Food Intake and Food Cravings Change during the Menstrual Cycle of Young Women?

Abstract: Objective The aim of the present study was to assess the anthropometric measures, food intake and food cravings during the menstrual cycle of undergraduate students of the faculty of nutrition. Methods A cross-sectional study was performed with 27 students from a public university in the state of Mato Grosso do Sul, Brazil, who had their food intake evaluated through a 24-hour food recall, their nutritional status evaluated based on anthropometric measures, and food cravings evaluated using the Foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
(58 reference statements)
4
14
0
3
Order By: Relevance
“…It was found that sweets had higher intake than that of other types of food in all menstrual phases. These results are similar to results of previous studies for increase in appetite (Gorczyca et al, 2015) and craving for sweets (Souza et al, 2018). We found significant associations of increased intake of sweets with depression, anger and sleepiness, being consistent with the results of a previous study showing that intake of sweets is linked with depressive symptoms (Knuppel et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was found that sweets had higher intake than that of other types of food in all menstrual phases. These results are similar to results of previous studies for increase in appetite (Gorczyca et al, 2015) and craving for sweets (Souza et al, 2018). We found significant associations of increased intake of sweets with depression, anger and sleepiness, being consistent with the results of a previous study showing that intake of sweets is linked with depressive symptoms (Knuppel et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…A study in 18-44-year-old women in the USA showed that there were significant increases in appetite, craving for chocolate and sweets in general, and craving for a salty flavor during the late luteal phase (Gorczyca et al, 2015). In Brazil, it was shown that the desire for foods rich in sugar, salt and fat was increased during the premenstrual period among university students (Souza et al, 2018). In Japan, 98% of nursing university students (mean age: 20.1 years) reported a desire for sweets and overeating as well as irritability and depression as the most frequent symptoms (Fukuoka et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, craving for sweets such as chocolate, cake, Eastern sweets ( Kunafa and Baklava ) was commonly reported by study participants (about 71%). This is consistent with research on food craving during the menstrual cycle, with foods rich in sugar, fat, and salt, such as snacks, chocolate, pastries, and desserts were higher during the premenstrual period [83,84].…”
Section: Discussionsupporting
confidence: 91%
“…Çukurovalı et al 12 determined that 62.0% of individuals had elevated appetite during premenstrual period and 52.0% of the individuals stated that in PMS, they had a tendency towards foods, that were not consumed regularly. In a study of Bronzi de Souza et al 19 , the desire for foods rich in sugar, salt, and fat, such as chocolate, pastries, snacks and desserts were found much higher (p < 0.05) during PMS, although it did not reflect neither a higher energy intake nor an alteration in the distribution of macronutrients. In our study, 66.2% of individuals experienced appetite changes and 42.5% craved for foods they did not consume usually in the premenstruation period, similar to other studies.…”
Section: Discussionmentioning
confidence: 88%